Kislovodsk, Russische Föderation: Spätbronzezeitliche Fundplätze im kaukasischen Hochgebirge - Reinhold, Sabine (e-Forschungsberichte des DAI, 2023)
From 2004 to 2010 archaeological sites of a so far unknown Late Bronze Age culture were investigated in the high mountain region south of the spa Kislovodsk (Stavropol‘ region, North Caucasus, Russia) (Fig. 1). Meanwhile, more than 260 sites are known from field surveys. In 2011, at one of these sites, dating to c. the second millennium BC (late Bronze Age), burials from the 5th century BC (late Scythian period) have been discovered. This coincidence is remarkable, since archaeological evidence of this period is extremely scarce, the site being the first ever found in the mountain area. The small necropolis of ten burials in stoneboxes and cairns contained a large and exquisite range of finds. The objects of outstanding quality are either the markers of an important trade route across the mountains or they can be considered as loot of a robbers’ band.